Acoustical Properties of Monochloroacetic Acid-Acetone-Water System at Different Temperatures. - NlKAM, P.S.; NEENA NIKAM, (MISS); HASAN, MEHDl; SURYAWANSHI, B.S. (Asian Journal of Chemistry, 2010)
Ultrasonic velocities in solutions of monochloroacetic acid(MCAA) in aqueous acetone mixtures were measured at 25ºC and 30ºC by using a single crystal interferometer at a frequency of 1.5 MHz. The ultrasonic velocity, density and concentration were used to calculate adiabatic compressibility, apparent molar compressibility, intermolecular free length, specific acoustic impedance, relative association and solvation number. Bachem and Gucker's laws have been found to be valid.